SIMULASI KARAKTERISTIK TERMAL PADA RUMAH BANJAR BUBUNGAN TINGGI DENGAN KOMPUTASI DINAMIKA FLUIDA - M Rizki Ikhsan; Madschen Sia Mei Ol Siska; Nur Hidayah (Scientific Journal of Mechanical Engineering Kinematika, 2021)
The Banjar traditional house with a high roof (Bubungan Tinggi) is a traditional house for the royal aristocracy. In modern times, this type of building is used as an architectural design for government buildings. Traditional house as a cultural heritage of local wisdom, where the house is designed to be able to adapt to the environment, so that people who are in it can feel comfortable. In this study, the thermal characteristics of the Banjar high ridge house were studied, using the CFD simulation method. The results obtained that the high ridge roof design is very beneficial in terms of absorption of solar energy, where the roof has a small geometric coefficient (Rb), so it is not exposed to much frontal sunlight. The shape of the high roof will also create a lot of shadows that shade the maximum. In the CFD simulation results, it was found that the high ridge roof became a cumulated place for hot air, due to the difference in pressure and bouyancy force, so that hot air would rise and collect on a higher roof. To avoid the accumulation of more hot air, mechanical modification that can be done is to install a blower that can blow hot air into the environment, so that it can help circulate air in the room.